ESP STUDENTS’ READINESS FOR LEARNER AUTONOMY: PUBLIC HEALTH STUDENTS PERCEPTIONS - Risa Arroyyani; Maryani, Maryani (Bajang Institute, 2024)
In English learning, students must have learner autonomy which means that they are responsible for their own learning by setting learning objectives, selecting learning methods, and evaluating progress. Autonomous learning also involves overcoming learning obstacles independently. This study aims to find out the public health students' perceptions of learner autonomy in English learning through descriptive statistics research, involving 66 respondents using questionnaires and interviews. Perceptions are evaluated in four categories of Learner Autonomy, namely Responsibility, Ability, Motivation, and Learning Activities. The results show that although students are highly motivated and perceived to be good in English ability, they remain teacher-centered and perceive that the teacher has greater responsibility for their learning. The outside-class learning activities were rated “very poor” to “poor” while inside-class learning activities were rated “poor” to “fair”. Public health students need to enhance their learner autonomy since they are good in some categories (ability and motivation), but poor in others (responsibility and learning activities).